ANALYSIS OF ACCOUNTING INFORMATION SYSTEM IMPLEMENTATION AT VILLAGE-OWNED ENTERPRISES - Rismawati, Mayada; Dunakhir, Samirah; Sahade, Sahade (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
This research aimed to analyze the implementation of accounting information systems in Village-Owned Enterprises of Bisaea in Lasalimu Village, Lasalimu Subdistrict, Buton Regency in Southeast Sulawesi. The variables of this research are the Accounting Information System in Village-Owned Enterprises. The population of this research is all data and documents related to the information system used by the Village-Owned Enterprises of Bisaea in Lasalimu Village, South Lasalimu Subdistrict, Buton Regency in Southeast Sulawesi, and the sample is all data and documents related to the accounting information system used by the Village-Owned Enterprises of Bisaea in Lasalimu Village, South Lasalimu Subdistrict, Buton Regency in Southeast Sulawesi for the year 2022. The data were collected by conducted using documentation. The data obtained were analyzed using a qualitative description. The results of this research suggest that in using the implementation of the accounting information system at Village-Owned Enterprises, Bisaea still applies manual recording; this is supported by the five components of the accounting information system, namely the user/person who operates the system, procedures and instructions, data, software, and internal controls for security measurements. As a result of the lack of employees, there are task traps on the part of the treasurer, secretary, recorder, and collector, which results in not working optimally; the solution must be to add employees according to their expertise in the field they are controlled so as not to cause task traps.